SIMULATION OF AIR HEAT TRANSFER IN CIRCULAR PIPES WITH TRIANGULAR AND SQUARE TURBULENCE STIMULATORS FOR HIGH REYNOLDS CRITERIA UP TO ONE MILLION - I. E. Lobanov (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. Conduct mathematical modeling of tornado zone structure systems between cyclic flow turbulence stimulators with the surface arrangement of triangular and square cross-sections based on multiblock computational techniques, based on solutions of the factorialized finite- volume procedure of the Reynolds equations (closed through the Menter shear stress transport model) and energy equations (on a multiscale  intersecting structured grid) at high Reynolds criteria Re=106 with an  exhaustive analysis of the relevant current lines. Methods. The calculations were carried out on a mathematical foundation based on the solution of the factorized finite-volume procedure of the Reynolds equations, which are closed using the low-Reynolds Menter shear stress transport model, and the energy equations on a multiscale  intersecting structured grid (factorized finite-volume procedure). Results. Mathematical simulations of the heat exchange process in straightand round horizontal pipes with turbulence stimulators with d/D=0.95...0.90 and t/D=0.25...1.00 of triangular and square transverse profiles with large Reynolds numbers (Re=106) on a foundation with multiblock computing technologies, which are based on solutions of factorized and finite-volume Reynolds equations and energy equations, were conducted. It was found that the relative intensification of heat transfer [(Nu/NuGL)|Re=106]/[(Nu/NuGL)|Re=105] in round pipes with square air turbulence stimulators for large Reynolds numbers (Re=106), which may be relevant in the channels used in heat exchangers, could be higher with a large-scale increment of hydraulic resistance than for slightly smaller numbers (Re=105), for relatively high flow turbulence stimulators d/D=0.90 for the entire range under consideration for the parameter of the relative step between them t/D=0.25...1.00 a little more than 3%; for triangular turbulence stimulators, the crosssection profiles have similar  values. For lower square turbulence stimulators with d/D=0.95, this increase  in relative heat transfer for large Reynolds numbers (Re=106) compared to smaller numbers (Re=105) does not exceed 6%; for triangular cross-section turbulence stimulators, similar indicators are slightly more  than 4%. Conclusion. The calculated results based on the developed model can optimize the intensification by turbulence stimulators and control the processes of heat transfer intensification. It is shown that for higher square  turbulence stimulators and higher Reynolds numbers, a limited increase in  the relative Nusselt criterion Nu/NuGL is accompanied by a significant increase in the relative hydro resistance due to the very significant influence  of return currents, which can flow directly on the turbulence stimulator to  the greater extent, the higher the Reynolds number; for triangular  turbulence stimulators, the above trend persists and even deepens.